Low-Dose Naltrexone for Pruritus in Systemic Sclerosis. (12th September 2011) - Frech, Tracy; Novak, Kirsten; Revelo, Monica P.; Murtaugh, Maureen; Markewitz, Boaz; Hatton, Nathan; Scholand, Mary Beth; Frech, Edward; Markewitz, David; Sawitzke, Allen D.
Abstract : Pruritus is a common symptom in systemic sclerosis (SSc), an autoimmune disease which causes fibrosis and vasculopathy in skin, lung, and gastrointestinal tract (GIT). Unfortunately, pruritus has limited treatment options in this disease. Pilot trials of low-dose naltrexone hydrochloride (LDN) for pruritus, pain, and quality of life (QOL) in other GIT diseases have been successful. In this case series we report three patients that had significant improvement in pruritus and total GIT symptoms as measured by the 10-point faces scale and the University of California Los Angeles Scleroderma Clinical Trials Consortium Gastrointestinal Tract 2.0 (UCLA SCTC GIT 2.0) questionnaire. This small case series suggests LDN may be an effective, highly tolerable, and inexpensive treatment for pruritus and GIT symptoms in SSc.